2021
DOI: 10.1097/gme.0000000000001834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep disturbances on employment and work productivity among midlife women in the US SWAN database: a brief report

Abstract: Objective: Menopause is associated with an increased prevalence of sleep difficulties. We evaluated the economic burden of sleep disturbances among working midlife women. Methods: This retrospective, longitudinal cohort study collected data from the US Study of Women's Health Across the Nation (SWAN) database of women age 42-52 years at enrollment. We assessed the association between sleep disturbances (trouble falling asleep, waking early, or nocturnal awakenings) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…While sleep quality, daytime fatigue, and workplace productivity share connections, precise quantification of relevant factors is complex and surprisingly difficult to study. Detailed research (Kagan et al, 2021) reported unemployment risk to be >30% higher for women with vs. without new-onset sleep disturbances. For women age 42-64 in USA, annual lost productivity attributed to sleep disorders exceeded $2B (Kagan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While sleep quality, daytime fatigue, and workplace productivity share connections, precise quantification of relevant factors is complex and surprisingly difficult to study. Detailed research (Kagan et al, 2021) reported unemployment risk to be >30% higher for women with vs. without new-onset sleep disturbances. For women age 42-64 in USA, annual lost productivity attributed to sleep disorders exceeded $2B (Kagan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed research (Kagan et al, 2021) reported unemployment risk to be >30% higher for women with vs. without new-onset sleep disturbances. For women age 42-64 in USA, annual lost productivity attributed to sleep disorders exceeded $2B (Kagan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems are associated with increased risks for chronic physical conditions (e.g., type 2 diabetes [Yao et al, 2021]), poor mental health (e.g., depression [Li et al, 2016]), and higher mortality (Li et al, 2014). Some literature also shows that sleep problems are risk factors for unemployment and decreased work productivity (Kagan et al, 2021). The deleterious effects of sleep problems at the individual and population levels may be particularly pronounced in LMICs, where the treatment and management of sleep problems are frequently insufficient (Arag on-Arreola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4 Sleep problems during menopause have been associated with approximately half an hour reduction in work time per week and an annual loss of $2.2 billion of productivity per year. 7 A study on self-perceived ability to perform in the job currently and for the next 2 years, reported that almost one third of female workers in the health sector were concerned about reduced work ability during menopause. 8 Half of employed women at 50 years of age are more likely to retire or work fewer hours per week due to distressing menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%